Job Satisfaction among School Teachers in Duwakot, Bhaktapur District, Nepal - Manandhar, Pratibha; Manandhar, Naresh; Joshi, Sunil Kumar (International Journal of Occupational Safety and Health, 2021)
Introduction: Job satisfaction is one of the determinant factors for professionals. The job satisfaction concerning school teachers reflects their strong motivation towards their job. This study aimed to measure the job satisfaction among teachers of Government and Private schools of Changu Narayan Municipality. Methods: A cross-sectional study was done at seven government and five private schools of wards no. 1 and 2 of Changu Narayan Municipality Bhaktapur District, Nepal over one month (20th April - 19th May 2021). Schools of Changu Narayan Municipality Ward No. 1 and 2 were purposively selected. The data was collected through validated questionnaire on Job Description Index (JDI)8 which consists of 17 domains. Data were entered in Excel and data analysis was done in SPSS version 20. Results: The overall job satisfaction was 65.77±11.52 which indicates that the majority of teachers were highly satisfied with their job. Conclusion: The findings of this study indicate job satisfaction among school level teachers was satisfied in their occupation especially in teaching profession. The domain sources of job satisfaction in school teachers appear to be work itself, coworker, relationship with students and sense of achievement. Whereas motivation in profession is most likely to be less job satisfaction among Government and Private schools.